Environmental challenges and perspectives of the fresh-cuts sector in Italy - Galioto, Francesco; Zucaro, Raffaella; Pergamo, Raffaella (Frontiers in Sustainable Food Systems, 2022)
This perspective paper provides insights on the characteristics of the fresh-cut sector in Italy and on the key challenges that the sector is facing. Specifically, the paper investigates the factors that brought to the development of agro-industrial hubs for fresh-cuts, capable of influencing the income and employment of various local communities in Italy and the factors that contributed causing serious environmental issues, especially related to the contamination of the environment with micro-plastics and to the consumption and pollution of water resources. Such issues were recently addressed through the Directive (EU) n. 904/2019 on the reduction of the impact of certain plastic products on the environment and through the Regulation (EU) 2020/741 on minimum requirements for water reuse. These regulations require a serious reflection on the strategies to be undertaken for the future of the sector, avoiding, or limiting, the risk of damaging the sector itself and, especially, the surrounding economic context. The paper concludes with some policy recommendation to overcome existing barriers and, eventually, transform them into opportunities.